Wheezing-Related Relevant Factors and the Role of Viral Bronchiolitis - Teijeiro, Alvaro; Gómez, R. Maximiliano (Frontiers in Allergy, 2021)
Bronchiolitis is a virus-associated infection of the lower respiratory tract exhibiting signs and symptoms of airway obstruction. Respiratory Syncytial Virus (RSV) is responsible in most cases; however, different rhinoviruses have also been implicated. Specific viruses and time until the first infection, severity of the respiratory condition, and atopic status have a determinant role in the recurrence of wheezing and asthma development. Genetics, lung function, atopic condition, the role of microbiota and environment, pollution, and obesity are considered in the present review. Emergency room visits and hospitalizations because of severe wheezing and smoking during pregnancy among others were identified as risk factors for significant morbidity in our population. Approaching determinant conditions like genetics, allergy, antiviral immunity, and environmental exposures such as farm vs. urban and viral virulence provides an opportunity to minimize morbidity of viral illness and asthma in children.